Effect of water restriction on nutrient utilization in pack camels under hot humid condition - RAI, A K; NAGPAL, A K; KHANNA, N D (The Indian Journal of Animal Sciences, 2013)
Adult male camels (6) of Bikaneri breed aged 8-11 years were managed under similar conditions. They were divided into 2 groups of 3 each. They were loaded with 100 kg baggage and made to walk for 2 hr dally. Group 1 on twice weekly watering schedule served as control while group 2 (expenmental) was deprived of drinking water for 10 days .and offered ad lib. water on eleventh day. The camels lost 21.8% body weight on 10 days dehydration. The DM intake of experimental camels fifth day onwards reduced to negligible quantity. The digestibility of all the proximate components showed continuous decline with increasing dehydration period and became negative from fourth day onward The laecal and urinary nitrogen excretion (g/day) decreased by 91.6 and 34.7%, respectively, on the last day at dehydration. The nitrogen balance and retention was negative. The digestibility coeffiCients of all the proximate components after 72 hr of once watering reached almost the initial levels, the daily nitrogen make and excretion through faeces and urine was 42.6, 34.9 and 217.7%, eespectively, of first day value. The improvements in nutrient intake vaded form 44 to 55%. The camels regained 48.1 % of the tost weight. The results suggested thaI the working pack camels on dehydration efficiently maintained nonnal metabolism up to fourth day and further dehydration depressed DMI and digestibility. Rehydration after 10 days of experimental dehydration improved the mctabolic profile hut did not attain normalcy even after 72 hr of watering.